2014
DOI: 10.3109/0284186x.2014.953259
|View full text |Cite
|
Sign up to set email alerts
|

Changes in skeletal muscle mass during palliative chemotherapy in patients with advanced lung cancer

Abstract: Almost half of the patients had stable or increased muscle mass during chemotherapy without receiving any cachexia treatment. Nearly all of these patients responded to the chemotherapy. Increase in muscle mass, but not sarcopenia at baseline, was a significant prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
161
6
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(194 citation statements)
references
References 24 publications
20
161
6
7
Order By: Relevance
“…The importance of sarcopenia has scarcely been studied in ovarian cancer, and these results have yet to be confirmed in international prospective trials. However, similar results have been found for other cancer types; stable or increasing muscle mass has been reported to relate to a prolonged survival in non‐small cell lung cancer, pancreatic cancer, and colorectal cancer, while a low muscle mass at baseline showed no prognostic significance 6, 7, 8…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The importance of sarcopenia has scarcely been studied in ovarian cancer, and these results have yet to be confirmed in international prospective trials. However, similar results have been found for other cancer types; stable or increasing muscle mass has been reported to relate to a prolonged survival in non‐small cell lung cancer, pancreatic cancer, and colorectal cancer, while a low muscle mass at baseline showed no prognostic significance 6, 7, 8…”
Section: Introductionsupporting
confidence: 65%
“…External validation of these findings in patients with other gynaecological malignancies and ovarian cancer specifically is imperative. Comparable results have been reported for patients with lung cancer, pancreatic cancer, and colorectal cancer, but these populations were primarily comprised of male patients and translation of these results to female patients—with lower muscle mass in general—should be applied carefully 6, 7, 8…”
Section: Discussionmentioning
confidence: 97%
“…Sarcopenia and myosteatosis have been significantly associated with a range of adverse outcomes including increased rate of post‐operative complications,10, 11, 40, 41, 42 longer length of hospital stay,41, 43 30‐day post‐operative mortality and in‐hospital mortality,44 and dose‐limiting toxicities 5, 6, 7, 8, 45, 46, 47, 48, 49, 50. In addition, the conditions have been demonstrated as independent predictors of reduced overall survival 18, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64. The situation is further complicated by the obesity epidemic that has been progressively worsening in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…Stene et al have also suggested that achieving tumor control might reverse the catabolic processes involved in cancer cachexia (18). Although their study was small, they observed that 16 of 35 stage IV NSCLC patients maintained or gained cross sectional muscle mass at the level of the third lumbar vertebra while receiving chemotherapy, and it's interesting that almost all of these patients (14 mof 16) had tumor remission as defined by RECIST v 1.1 criteria (18). If tumor regression/control reverse cancer cachexia, it's conceivable that treatments which target cachexia might inhibit a tumor's growth by reducing its energy sources and precursors of macromolecules (19).…”
mentioning
confidence: 99%